2020
DOI: 10.3390/cells9041042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of the RhoGAP GRAF3 and Its Capacity to Limit Blood Pressure In Vivo

Abstract: Anti-hypertensive therapies are usually prescribed empirically and are often ineffective. Given the prevalence and deleterious outcomes of hypertension (HTN), improved strategies are needed. We reported that the Rho-GAP GRAF3 is selectively expressed in smooth muscle cells (SMC) and controls blood pressure (BP) by limiting the RhoA-dependent contractility of resistance arterioles. Importantly, genetic variants at the GRAF3 locus controls BP in patients. The goal of this study was to validate GRAF3 as a druggab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…To this end, a previous study found that GRAF3 -deficient mice exhibited increased susceptibility to DOCA-salt-mediated hypertension [ 28 ]. Results from another in-vivo mouse model showed that even modest induction of GRAF3 in smooth muscle cells significantly decreased basal BP and vasoconstrictor-induced hypertension, indicating that allosteric activators of GRAF3 are targeted antihypertensive drugs [ 29 ]. Therefore, apatinib could be acting by first activating RhoA via GRAF3 inhibition thereby causing vascular remodeling, as evidenced by expression of collagen and increased media thickness of mid-aorta.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a previous study found that GRAF3 -deficient mice exhibited increased susceptibility to DOCA-salt-mediated hypertension [ 28 ]. Results from another in-vivo mouse model showed that even modest induction of GRAF3 in smooth muscle cells significantly decreased basal BP and vasoconstrictor-induced hypertension, indicating that allosteric activators of GRAF3 are targeted antihypertensive drugs [ 29 ]. Therefore, apatinib could be acting by first activating RhoA via GRAF3 inhibition thereby causing vascular remodeling, as evidenced by expression of collagen and increased media thickness of mid-aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ARHGAP32 has been mainly investigated in the regulation of blood pressure. Rho-speci c GTPase-activating protein GRAF3 was highly expressed in smooth muscle cells (SMCs) and regulated blood pressure control by inhibiting the contractility of RhoA-mediated SMC 25 . GRAF3-de cient mice also showed increased blood pressure in response to angiotensin II and endothelin 1 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetically modified mice were used to establish that ARHGAP42 deficiency results in hypertension via increased response to angiotensin II and endothelin‐1 [74]. These models are continuing to be applied to assess whether this candidate gene could be a valid drug target moving forward [75]. Nonetheless, functional validation represents a major challenge due to the large number of SNPs associated with BP.…”
Section: Risk Prediction and Causal Mechanismsmentioning
confidence: 99%